Euro or not Euro - that is not the question! Economic well-being and the fate of the European Monetary Union - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2014)
It will be argued that it is not of fundamental importance for growth and employment whether the EU clings to the Euro or allows for a dissolution of the Eurozone and a reemergence of national currencies but how multi-level macroeconomic coordination of different policy areas and nation-states will be achieved. Given that this insight is based on an alternative economic reasoning which is (still) not the common view of most political and economic actors relevant in the EU, it will be analysed under which conditions it would be recommendable to maintain the Euro or to reestablish national currencies.
Keywords: F15; P16; 330; european integration; neo-functionalism; neo-realism